Tigridia gracielae (Tigridieae: Iridaceae), a new species from Mexico - Rodríguez, Aarón; Ortiz-Catedral, Luis (Instituto de Ecología, A.C., 2003)
Tigridia gracielae (Tigridieae: Iridaceae), from the state of México, is a new species morphologically similar to T. venusta, from the state of Michoacán. Tigridia gracielae differs from T. venusta in having shorter and narrower tepals, a longer staminal column, anthers fertile along their full length and shorter style branches. Both species share habitat preference for the shaded understory of fir and pine forests near 3000 m elevation.